Elsewhere - Koontz, Dean R. (Dean Ray), 1945- (Thomas & Mercer, 2020)
"Since his wife, Michelle, left seven years ago, Jeffy Coltrane has worked to maintain a normal life for himself and his eleven-year-old daughter, Amity, in Suavidad Beach. It's a quiet life, until a local eccentric known as Spooky Ed shows up on their doorstep. Ed entrusts Jeffy with hiding a strange and dangerous object-something he calls "the key to everything"-and tells Jeffy that he must never use the device. But after a visit from a group of ominous men, Jeffy and Amity find themselves accidentally activating the key and discovering an extraordinary truth. The device allows them to jump between parallel planes at once familiar and bizarre, wondrous and terrifying. And Jeffy and Amity can't help but wonder, could Michelle be just a click away? Jeffy and Amity aren't the only ones interested in the device."
Keywords: Government investigators -- Fiction; Space and time -- Fiction; Fourth dimension -- Fiction; Science fiction; Thrillers (Fiction)